What works and why? Lessons from public management reform in in Malaysia - Siddiqueea, Noore Alam; Xavier, John Antony; Mohamed, Mohd Zin (Routledge Taylor & Francis Group, 2019)
This article examines the Malaysian experience with public management reform to verify arguments about various reform models. Drawing on empirical data, it investigates reforms that have worked and those that have had limited impacts on public service improvements. It identifies critical success factors that determine reform outcomes and concludes that for reforms to succeed a combined top–down and bottom–up approach is crucial. It argues that while diagnostic and problem-oriented reforms have a better chance of being successful, the value of best-practice reforms should not be discounted. The cumulative impact of such reforms can be significant, as the Malaysian case demonstrates.